2012
DOI: 10.1179/1743294411y.0000000015
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial hardening of duplex 2205 stainless steel by low temperature carburisation: enhanced mechanical and electrochemical performance

Abstract: The mechanical properties and corrosion resistance of duplex (ferrite-austenite) grade 2205 stainless steel have been substantially improved by interstitial hardening using low temperature carburisation. The austenite phase of the duplex stainless steel responds to low temperature carburisation in a similar manner as single phase austenitic stainless steels, forming 'expanded' austenite (also called S phase). The surface layer that forms on the ferritic portion of 2205 steel consists of a paraequilibrium carbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Low-temperature carburization or nitridation are effective ways to improve surface properties and corrosion resistance of stainless steels [7][8][9][10][11][12][13]. For PH 13-8 Mo stainless steel, a significant increase of surface hardness and corrosion resistance was achieved after low-temperature carburization [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-temperature carburization or nitridation are effective ways to improve surface properties and corrosion resistance of stainless steels [7][8][9][10][11][12][13]. For PH 13-8 Mo stainless steel, a significant increase of surface hardness and corrosion resistance was achieved after low-temperature carburization [13].…”
Section: Introductionmentioning
confidence: 99%
“…As aging proceeds, the fractions of Ni and Al increases and the Ni-to-Al ratio approaches unity [2,3]. The NiAl precipitates are nanometer-sized, spherical, and coherent with the ferrite-or martensite matrix [6].Low-temperature carburization or nitridation are effective ways to improve surface properties and corrosion resistance of stainless steels [7][8][9][10][11][12][13]. For PH 13-8 Mo stainless steel, a significant increase of surface hardness and corrosion resistance was achieved after low-temperature carburization [13].…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] As implied by the name, carbon and nitrogen reside in interstitial lattice sites. The surface alloyed region, the case, ranges in thickness between 5 and 30 μm depending on treatment time and temperature.…”
mentioning
confidence: 99%
“…19,21 In previous work, it was shown that the inherently good pitting resistance of DSS alloy 2205 was retained while increasing the crevice corrosion and fatigue resistance. 25 The inherent pitting resistance (high value of Epit) of alloy 2205 is a result of high concentrations of passivity-promoting alloying elements. As discussed above, when a stainless steel becomes sensitized, the alloying elements (i.e., Cr) that provide passivity, in addition to being strong carbide formers, are depleted in the regions adjacent to where the new phases form.…”
mentioning
confidence: 99%
See 1 more Smart Citation